Dissolution of Metals from Biosolid-Treated Soils by Organic Acid Mixtures - Won-Pyo Park; Bon-Jun Koo; Andrew C. Chang; Thomas E. Ferko; Jonathan R. Parker; Tracy H. Ward; Stephanie V. Lara; Chau M. Nguyen (Applied and Environmental Soil Science)
Results for the solubilization of metals from biosolid- (BSL-) treated soils by simulated organic acid-based synthetic root exudates (OA mixtures) of differing composition and concentrations are presented. This study used two BSL-treated Romona soils and a BSL-free Romona soil control that were collected from experimental plots of a long-term BSL land application experiment. Results indicate that the solubility of metals in a BSL-treated soil with 0.01 and 0.1 M OA mixtures was significantly higher than that of 0.001 M concentrations. Differences in composition of OAs caused by BSL treatment and the length of growing periods did not affect the solubility of metals. There were no significant differences in organic composition and metals extracted for plants grown at 2, 4, 8, 12, and 16 weeks. The amount of metals extracted tended to decrease with the increase of the pH. Results of metal dissolution kinetics indicate two-stage metal dissolution. A rapid dissolution of metals occurred in the first 15 minutes. For Cd, Cu, Ni, and Zn, approximately 60–70% of the metals were released in the first 15 minutes while the initial releases for Cr and Pb were approximately 30% of the total. It was then followed by a slow but steady release of additional metals over 48 hours.